2017
DOI: 10.1007/s10461-017-1873-8
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Douching Among Men Who Have Sex with Men in Paris: Implications for HIV/STI Risk Behaviors and Rectal Microbicide Development

Abstract: Rectal douching is a common but potentially risky practice among MSM; MSM who douche may be ideal candidates for rectal microbicides as HIV prevention. Herein we explored rectal douching and its association with condomless receptive anal intercourse (CRAI), group sex, rates of HIV and other STIs, and likelihood to use rectal microbicide gels. We recruited a sample of 580 MSM from a geosocial-networking smartphone application in Paris, France in 2016. Regression models estimated adjusted risk ratios (aRRs) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…As reported in prior research, 18 in October 2016 we surveyed users of a popular GSN smartphone application among MSM via broadcast announcements in the Paris metropolitan area; 580 MSM completed the survey. After obtaining sociodemographic information (age, employment status, born in France or elsewhere, sexual orientation, relationship status), we assessed the following during the previous 3 months: popper use (any vs none), use of drugs or alcohol during sex (none, any, three to five times, six or more times), condomless insertive and receptive intercourse (any vs none) and group sex (never, within the past 3 months, before the past 3 months).…”
Section: Methodsmentioning
confidence: 99%
“…As reported in prior research, 18 in October 2016 we surveyed users of a popular GSN smartphone application among MSM via broadcast announcements in the Paris metropolitan area; 580 MSM completed the survey. After obtaining sociodemographic information (age, employment status, born in France or elsewhere, sexual orientation, relationship status), we assessed the following during the previous 3 months: popper use (any vs none), use of drugs or alcohol during sex (none, any, three to five times, six or more times), condomless insertive and receptive intercourse (any vs none) and group sex (never, within the past 3 months, before the past 3 months).…”
Section: Methodsmentioning
confidence: 99%
“…These types of apps have rapidly been adopted as a means for GBM to meet sex partners, and offer important opportunities as recruitment venues for sexual health research studies. 9,[23][24][25][26][27][28][29] Despite the internet's and, more recently, apps' suitability for researchers to engage large numbers of geographically diverse GBM, 12,[30][31][32][33] public health researchers and practitioners remain concerned about adequate representation of those most vulnerable to HIV, including younger GBM and persons of color. 9,34 Historically, persons of color have been harder to recruit, engage, and retain in research studies, [35][36][37] and online-recruited studies have observed greater attrition among men of color during consecutive follow-up assessments.…”
Section: Introductionmentioning
confidence: 99%
“…These figures suggest that RD might be a common practice among MSM in urban China whatever their economic level. The prevalence of RD behavior among MSM in China is close to that of the USA (66%), Kenya (63%) [5,6], the UK, Brazil, and France (53.4-54.3%) [4,7,8], but greater than that in Peru (18.2-27.0%) [17,18] and the Netherlands (13.6-46%) [19,20]. Despite this high prevalence among MSM worldwide, scientific data for and knowledge of RD in the Chinese MSM population is still poor.…”
Section: Discussionmentioning
confidence: 86%
“…Men who have sex with men (MSM) are disproportionately affected by HIV in China and many other countries [1][2][3]. Understanding the sexual behaviors and preferences of this key population group is essential for developing effective prevention strategies [4]. In recent years, the rectal douching (RD) behavior of MSM has received widespread attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation